Stability comparison of two different dentoalveolar expansion treatment protocols - Ezgi Atik; Tülin Taner (Dental Press Journal of Orthodontics)
ABSTRACT Objective: The aim of this study was to compare the longitudinal stability of the conventional straight-wire system after the use of a quad-helix appliance with Damon self-ligating system in patients with Class I malocclusion. Methods: 27 adolescent patients were evaluated at three different periods: pre-treatment (T1), post-treatment (T2) and three years post-treatment (T3). Group 1 included 12 patients (with a mean age of 14.65 year) treated with Damon 3MX bracket system; and Group 2 included 15 patients (with a mean age of 14.8 year) who underwent orthodontic treatment with Roth prescribed brackets after expansion with Quad-Helix appliance. Relapse was evaluated with dental cast examination and cephalometric radiograph tracings. Statistical analysis was performed with IBM-SPSS for Windows software, version 21 (SPSS Inc., Chicago, IL). A p-value smaller than 0.05 was considered statistically significant. Results: There were significant increases in all transverse dental and postero-anterior measurements (except for UL6-ML mm in Group 1) with active treatment. There was some significant relapse in the long-term in inter-canine width in both groups and in the inter-first premolar width in Group 2 (p< 0.05). Significant decrease in all frontal measurements from T2 to T3 was seen for both groups. Upper and lower incisors significantly proclined in T1-T2 (p<0.05), however no relapse was found for both groups. When two systems were compared, there was no significant difference for the long-term follow-up period. Conclusion: Conventional (quad-helix appliance with conventional brackets) and Damon systems were found similar with regard to the long-term incisor positions and transverse dimension changes of maxillary arch.